Energy spectrum analysis for intense pulsed electron beam. (28th November 2016) - Shen, J.; An, H.H.; Liu, H.Y.; Remnev, G.E.; Nashilevskiy, A.V.; Li, D.Y.; Zhang, J.; Zhong, H.W.; Cui, X.J.; Liang, G.Y.; Qu, M.; Yan, S.; et al.
Abstract: As the energy spread of intense pulsed electron beams (IPEB) strongly influences the irradiation effects, it has been of great importance to characterize the IPEB energy spectrum. With the combination of Child–Langmuir law and Monte Carlo simulation, the IPEB energy spectrum has been obtained in this work by transformation from the accelerating voltage applied to the diode. To verify the accuracy of this simple algorithm, a magnetic spectrometer with an imaging plate was designed to test the IPEB energy spectrum. The measurement was completed with IPEB generated by explosive emission electron diode, the pulse duration, maximum electron energy, total beam current being 80 ns, 450 keV, and 1 kA, respectively. The results verified the reliability of the above analysis method for energy spectrum, which can avoid intercepting the beam, and at the same time significantly improved the energy resolution. Some calculation and experimental details are discussed in this paper.